(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Traditional Siddha medicine offers a vast array of polyherbal formulations used effectively in the treatment of various ailments. One such formulation is Kalladaippu Kudineer Chooranam, traditionally used in the management of urinary calculi (Kalladaippu). This study aims to evaluate the phytochemical constituents and physicochemical properties of Kalladaippu Kudineer Chooranam to scientifically validate its therapeutic potential and ensure quality control. The formulation was prepared according to classical Siddha literature and subjected to preliminary phytochemical screening, which revealed the presence of alkaloids, flavonoids, tannins, saponins, glycosides, and phenolic compounds- indicating significant therapeutic potential such as anti-inflammatory, diuretic, and lithotriptic activities. Physicochemical parameters including organoleptic properties, total ash, acid-insoluble ash, water-soluble ash, loss on drying, and extractive values (water and alcohol soluble) were determined using standard methods. The results were within acceptable limits, suggesting the formulation’s purity and stability. This dual evaluation ensures the standardization and authenticity of the formulation, supporting its traditional claims with scientific evidence. The presence of multiple bioactive compounds highlights the formulation’s potential for further pharmacological and clinical investigations. Thus, the study provides a foundation for the integration of Kalladaippu Kudineer Chooranam into evidence-based practice and contributes to the preservation and validation of Siddha medicine.